Efficacy of integrating short-course chemotherapy with Chinese herbs to treat multi-drug resistant pulmonary tuberculosis in China: a study protocol - Shun-Xian Zhang; Lei Qiu; Cui Li; Wei Zhou; Li-Ming Tian; Hui-Yong Zhang; Zi-Feng Ma; Xian-Wei Wu; Xing Huang; Yu-Wei Jiang; Shao-Yan Zhang; Zhen-Hui Lu (BMC, 2021)
Abstract Background Tuberculosis (TB) caused Mycobacterium tuberculosis (M.tb) is one of infectious disease that lead a large number of morbidity and mortality all over the world. Although no reliable evidence has been found, it is considered that combining chemotherapeutic drugs with Chinese herbs can significantly improves the cure rate and the clinical therapeutic effect. Methods Multi-drug resistant pulmonary tuberculosis (MDR-PTB, n = 258) patients with Qi-yin deficiency syndrome will be randomly assigned into a treatment group (n = 172) or control/placebo group (n = 86). The treatment group will receive the chemotherapeutic drugs combined with Chinese herbs granules (1 + 3 granules), while the control group will receive the chemotherapeutic drugs combined with Chinese herbs placebo (1 + 3 placebo granules). In addition, MDR-PTB (n = 312) patients with Yin deficiency lung heat syndrome will be randomly assigned to a treatment (n = 208) or control/placebo (n = 104) group. The treatment group will receive the chemotherapeutic regimen combined with Chinese herbs granules (2 + 4 granules), while the control group will receive the chemotherapeutic drugs and Chinese herbs placebo (2 + 4 placebo granules). The primary outcome is cure rate, the secondary outcomes included time to sputum culture conversion, lesion absorption rate and cavity closure rate. BACTEC™ MGIT™ automated mycobacterial detection system will be used to evaluate the M.tb infection and drug resistance. Chi-square test and Cox regression will be conducted with SAS 9.4 Statistical software to analyze the data. Discussion The treatment cycle for MDR-PTB using standardized modern medicine could cause lengthy substantial side effects. Chinese herbs have been used for many years to treat MDR-PTB, but are without high-quality evidence. Hence, it is unknown whether Chinese herbs enhances the clinical therapeutic effect of synthetic drugs for treating MDR-PTB. Therefore, this study will be conducted to evaluate the clinical therapeutic effect of combining Chinese herbs and chemotherapeutic drugs to treat MDR-PTB cases. It will assist in screening new therapeutic drugs and establishing treatment plan that aims to improve the clinical therapeutic effect for MDR-PTB patients. Trial registration This trial was registered at ClinicalTrials.gov (ChiCTR1900027720) on 24 November 2019 (prospective registered). Graphical Abstract